HIGHER ORDER THINKING SKILLS AND NEW NORMAL TEACHING STRATEGIES IN THE PROVINCE OF CAPIZ - Arroyo, Joey D. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This descriptive-correlational study was conducted to determine the level of higher order thinking skills and new normal teaching strategies of HEI faculty in the Province of Capiz. Mixed methods of research employing quantitative and qualitative approaches in gathering the data were used. A random sample of 554 HEI faculty from the Province of Capiz were chosen as respondents of the study. A researcher – made questionnaire was used to gather needed data. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t – test, Analysis of Variance and Spearman rank correlation analysis. The findings of the study revealed that HEI faculty had a very good level of higher order thinking skills as a whole and in terms of analysis, evaluation and creation. Also, they had very good degree of new normal teaching strategies as a whole and in terms of online and non-online approaches. Demographic profile such as age, sex, educational attainment and academic rank tended to affect the level of higher order thinking skills of HEI faculty. On the other hand, length of service did not affect the level of higher order thinking skills of HEI faculty. New normal teaching strategies of HEI faculty significantly differed in terms of various demographic profile such as age, sex, educational attainment, length of service in years and academic rank. Lastly, the level of higher order thinking skills was found to significantly affect the teachers’ new normal teaching strategies. Some recommendations were laid by the researchers to promote and foster higher order thinking skills and new normal teaching strategies among HEI faculty.